2021
DOI: 10.3322/caac.21694
|View full text |Cite
|
Sign up to set email alerts
|

Intermittent fasting in the prevention and treatment of cancer

Abstract: Chronic caloric restriction (CR) has powerful anticarcinogenic actions in both preclinical and clinical studies but may be difficult to sustain. As an alternative to CR, there has been growing interest in intermittent fasting (IF) in both the scientific and lay community as a result of promising study results, mainly in experimental animal models. According to a survey by the International Food Information Council Foundation, IF has become the most popular diet in the last year, and patients with cancer are se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(109 citation statements)
references
References 195 publications
(252 reference statements)
1
91
0
3
Order By: Relevance
“…For instance, depleting dietary glucose (a key oncometabolite) through low carbohydrate, ketogenic diets has been shown to have positive effects in patient survival, tumor sensitization, and tumor shrinkage [13,193]. Similarly, caloric restriction, intermittent fasting, or the deprivation of certain "oncogenic" amino acids in the diet has also been shown to have positive effects in cancer for various animal models and in some cancer patients [194][195][196][197]. Likewise, the addition of certain basic compounds (such as bicarbonate, lysine, or Tris) in the diet to buffer against the effects of lactate and the general tumor acidosis has shown some unexpected benefits in both animal tumor models and in some cancer patients [198][199][200].…”
Section: Connecting the Multiple Views Of Cancer Through Metabolomicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, depleting dietary glucose (a key oncometabolite) through low carbohydrate, ketogenic diets has been shown to have positive effects in patient survival, tumor sensitization, and tumor shrinkage [13,193]. Similarly, caloric restriction, intermittent fasting, or the deprivation of certain "oncogenic" amino acids in the diet has also been shown to have positive effects in cancer for various animal models and in some cancer patients [194][195][196][197]. Likewise, the addition of certain basic compounds (such as bicarbonate, lysine, or Tris) in the diet to buffer against the effects of lactate and the general tumor acidosis has shown some unexpected benefits in both animal tumor models and in some cancer patients [198][199][200].…”
Section: Connecting the Multiple Views Of Cancer Through Metabolomicsmentioning
confidence: 99%
“…Likewise, the addition of certain basic compounds (such as bicarbonate, lysine, or Tris) in the diet to buffer against the effects of lactate and the general tumor acidosis has shown some unexpected benefits in both animal tumor models and in some cancer patients [198][199][200]. In many cases, the anticancer effects of these dietary modifications were amplified with the inclusion of more conventional chemotherapies or antimetabolite therapies [196,200] Metabolomics has also enabled the identification and mechanistic characterization of metabolites or dietary compounds that are anti-oncometabolites or cancer preventing agents. For instance, metabolome-wide association studies have shown that individuals with high plasma levels of vitamin C, carotenoids, and alpha-tocopherol were protected against gastric cancer [201], while those with high calcium and vitamin D levels were protected against colorectal cancer [201].…”
Section: Connecting the Multiple Views Of Cancer Through Metabolomicsmentioning
confidence: 99%
“…Since ancient times, worldwide religions have advocated for food restriction (FR) due to its physical and psychological benefits [ 1 , 2 , 3 ]. However, the health benefits owing to FR have only in recent years been supported by scientific evidence.…”
Section: Introductionmentioning
confidence: 99%
“…Calorie restriction (CR) is a commonly used FR strategy that restricts everyday energy intake without incurring malnutrition [ 4 ]. In experimental animal models, appropriate CR has been shown to have benefits including elongation of life span [ 5 ], promotion of weight loss [ 6 , 7 , 8 ], suppression of inflammation [ 9 , 10 , 11 ], cardiovascular disease risk reduction [ 12 , 13 , 14 ], and cancer prevention [ 2 , 15 ]. Notwithstanding these benefits, there are still concerns when applying CR, such as poor CR compliance [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation